POTENSI KETERSEDIAAN LIMBAH TANAMAN PANGAN SEBAGAI PAKAN TERNAK SAPI POTONG DI KABUPATEN MUNA BARAT - Muhsafaat, La Ode; Mpia, La; R, Mustafa. (Program Studi Agribisnis Fakultas Pertanian, 2024)
West Muna Regency in Southeast Sulawesi Province is a new autonomous region where the majority of the population is engaged in plantation, agriculture, livestock, and fisheries sectors. In the livestock sector, the population of beef cattle in this area reached 23,388 heads in 2023. However, cattle rearing still depends on natural forage whose production is limited due to seasonal changes and land conversion. This research aims to analyze the potential of food crop waste as a source of feed for beef cattle in West Muna Regency, using secondary data from BPS West Muna in 2023, with descriptive analysis methods. Data analysis is based on calculations of livestock units (ST), food crop waste dry matter (BK), waste carrying capacity and waste carrying capacity index (IDD). The analysis results show that the harvested area for food crops is 9,671 ha with the main commodities being corn (6,372.6 ha), peanuts (1,607.6 ha) and rice (1,048.9 ha). The potential of dry matter from food crop waste reaches 33,221.7 tons of DM/year, with the largest contribution from corn (28,676.7 tons of DM/year). West Muna Regency has an IDD for feed from food crop waste of 0.89, which shows that 89% of beef cattle feed needs can be met from food crop waste. Four sub-districts have an IDD of more than 1, namely Wadaga, Lawa, Barangka, and Sawerigadi, indicating the potential for dry mater from feed crop waste to exceed the needs of the beef cattle population in these sub-districts. The sub-districts with the lowest IDD are Napano Kusambi, Tiworo Tengah, Tiworo Pulau, and Tiworo Utara.